Improving Attractivity of Passenger Information Systems for Metro Passengers (Current Problems in Rail Vehicles, 2021)
Modern passenger information system for metro – PIS+, concrete project implementation. Wayfinding capabilities of transfer connections. Orientation and navigation for people with reduced mobility. Passenger flow optimalization within the metro stations. Dynamic updates from the “Train office”.
Keywords: information system; metro; orientation; navigation; people with reduced mobility